Stigma Masyarakat terhadap Pasien Positif COVID-19 - Nofriawan, Tri; Wahyuni, Sri; Indrianti, Ganis (Jurnal Kesehatan Holistic, 2022)
Introduction: Covid-19 is an infectious disease that can spread quickly, this can cause social stigma in the community regarding Covid-19 and can make things worse because individuals have excessive fear and worry about Covid-19.. Objective: This study aims to look at the stigma of society towards positive Covid-19 patients. Methods: This study uses a descriptive design with a cross sectional form. The number of samples in this study was 140 respondents with simple random sampling technique. Result: The results of this study were as many as 52.1% of the people in the West Sidomulyo Village gave a stigma to positive Covid-19 patients. and not worrying about Covid-19 so that health care can still be carried out. Conclusion: It can be said that there are still many people who have stigma against Covid-19 patients, this is a challenge for health workers to make people feel safe and not worry about Covid-19 so that health care can still be carried out.